Poder Legislativo no Ceará: geografia do voto e ação política na Assembleia Legislativa - Vieira, Márcia Paula Chaves (2012)
The research aims to observe whether the political actions of the representatives at the Legislative Assembly of the State of Ceará were directed to the municipalities in which they obtained most of their vote and how was their relationship with their political parties. Politicians fulfill their term of office in order to be granted a new mandate in the next election. This mandate might be a renewed one at the Legislative Assembly or a new mandate at another political office. The political geography of the Assembly elections was analyzed to understand the relationship between vote distribution and the type o parliamentary activity. A typology of vote distribution was elaborated leading to the conclusion that there are informal territorial constituencies and that most politicians guide their actions towards these constituencies.